The impact of age, gender and anxiety on the english learner class participation. Case of seventh graders in the school District 0602 (morning shift) in The City of San Salvador during the academic year 2014 - Escobar Ibarra, Guillermo; Leonor Umanzor, Jenifer (2024)
Learning a foreign language is really important that students have an active oral participation when being embarked on that process. According to Ghobadi, participation is an essential part in the learning process that provides the students with opportunities to learn, practice, and improve the language (Turner, 2004). Some specialists such as Block are concerned that it is necessary for students to get involved in classes since participation and the learning process are intimately intertwined. But, unfortunately, participation has been affected by a variety of different factors through the years. In her research about Factors Affecting on Oral Participation of ELT Students and Language Development, Ghobadi (2012) categorizes age, gender, and anxiety as ones of the factors that interfere most with the learners’ participation. For that reason, one of the main purposes of this investigation was to synthesize and explain how age, gender, and anxiety interfere with the students’ participation as well as their learning process. Because through the literature review in the web, books, theses, and essays from the Central Library of the UES, the research team could find huge data of how these variables interfere with the students’ participation. Then, the researchers investigated how these three factors were influencing on the participation of the corresponding sample under study by using a checklist and administrating questionnaires to the students in order to identify and know how these three variables are affecting the students ́ performance. And at the end, they analyzed the data with the final objective to provide possible recommendations to the schools under study.